Understanding EFL international students academic listening strategies: a literature review - Salim Halali, Ahlam Ali; Ismail, Lilliati; Abd Samad, Arshad; Razali, Abu Bakar; Noordin, Nooreen (Tresorix Ltd, 2022)
. Academic listening and interaction in international educational settings are essential for academic success. International students’ language proficiency and prior practice in their home countries either facilitate or impede their academic success. Thus, internationalization has become a desirable trend among learners to further their studies in overseas institutions where English is the medium of instruction. Overseas education allows international students to gain new knowledge and improve their academic skills in various academic fields. However, a lack of English communicative competence and comprehension impedes learners’ academic and communicative success. As a result, international students look for strategies to help them overcome their academic comprehension challenges. This paper explores and better explains EFL international students’ academic listening challenges and strategies to motivate stakeholders to support international students in furthering their studies overseas. Thus, this paper reviews related literature on academic listening strategies through the traditional literature review process. Therefore, this paper explores and better explains EFL international students’ academic listening challenges and strategies to motivate stakeholders to support international students in furthering their studies overseas. The discussion of findings reveals that international students face challenges with understanding others in academic discourse. These challenges are due to their lack of prior English listening practice in their home countries. Thus, international students rely on strategies to overcome communication challenges and improve academic listening comprehension skills (i.e., memory, cognitive, and social strategies). The findings should encourage administrators of international institutions, researchers, and other stakeholders to revamp pre-sessional English language programs and conduct more research on international students’ language learning experiences to help them succeed in their overseas study programs.